Adaptação transcultural e validação da escala childbirth fear prior to pregnancy (CFPP) para utilização no brasil - Tomazin, kelly Jaqueline da Costa Galinari [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Introdução: O enfermeiro tem reconhecimento mundial na mudança do modelo de assistência ao parto, resgatando o nascimento como um processo natural, no qual os sentimentos e preocupações da parturiente devem ser respeitados. Nesta perspectiva surge a preocupação com a formação acadêmica dos futuros enfermeiros. Entende-se que a forma como o profissional percebe o processo de nascimento pode influenciar a assistência. O medo e a interpretação desse período como sofrimento e dor podem estimular intervenções desnecessárias no intuito de abreviar vivências consideradas negativas. Considerando a inexistência de instrumento voltado para a população brasileira, capaz de avaliar o medo do parto antes da gestação, o objetivo do presente estudo foi realizar a adaptação transcultural e analisar as evidências de validade e confiabilidade da versão brasileira da Escala Childbirth Fear Prior to Pregnancy (CFPP). Método: Trata-se de estudo do tipo metodológico, aprovado pelo Comitê de Ética em Pesquisa da Faculdade de Medicina de Botucatu, parecer nº 2.428.902, com amostra de conveniência composta por 146 alunos de graduação de enfermagem. A adaptação transcultural da Versão Brasileira da escala seguiu as etapas amplamente utilizadas na literatura: Avaliação por comitê de especialistas e Pré-teste com avaliação da população alvo. Participaram do estudo 146 graduandos de enfermagem da Faculdade de Medicina de Botucatu – FMB e do Centro Universitário Católico Salesiano Auxilium – UniSALESIANO. Os dados foram coletados de fevereiro a agosto de 2018, fora das atividades letivas. A validade de face e conteúdo foi avaliada pelo comitê de juízes e a população alvo. A análise fatorial exploratória foi realizada para validade de constructo. A validade de critério concorrente divergente foi testada pela associação da medida dos escores obtidos da Versão Brasileira da CFPP com as subescalas de Depressão, Ansiedade e Stress, da EDAE - A. Para o cálculo da consistência interna foi realizado o alfa de Cronbach e a estabilidade testada através do teste-reteste. O nível de significância adotado foi de 0,05. Resultados: Há uma predominância de participantes do sexo feminino; com idade média de 21,2 anos; sem parceiro; de cor branca e com renda familiar média de R$ 3.550,43. A maioria não exercia atividade remunerada. Quanto ao ano cursado, 23,9% estava no primeiro ano; 24,6% no segundo ano; 21,2% no terceiro ano; 20,5% no quarto ano e 10,2% no quinto ano. A maioria não havia cursado a disciplina de Saúde da Mulher e não tinha assistido a um parto. A análise fatorial apresenta uma solução fatorial que confirma a unidimensionalidade do instrumento. As pontuações da Versão Brasileira da CFPP foram significativamente, mas fracamente correlacionadas com os escores da subescala EDAE-A (r=0,32, p<0,001), confirmando a validade de critério. Quanto à confiabilidade, foi obtido um valor adequado para consistência interna (Alfa de Cronbach 0,86). A estabilidade do instrumento foi considerada adequada, uma vez que os valores do Coeficiente de Correlação Intraclasse foi de 0,99 e estatisticamente significativo (p=0,000), os resultados obtidos demonstram assim, uma boa estabilidade temporal do instrumento. Conclusão: de acordo com a análise das propriedades psicométricas, a Versão Brasileira da CFPP é uma escala unidimensional de 10 itens, que apresenta boas evidências de validade e confiabilidade para medir o medo do parto em jovens adultos antes da gestação.

Introduction: The nurse has a world acknowledgement on changing birth assistance, recovering birth as a natural process as well as feelings and concerns from parturient being respected. Thus, an interest has been raised on nursing academic graduation. In addition, the meaning as a professional caring about the birthing process can influence the service. Fear, and the interpretation of this period as suffer and pain might stimulate unnecessary interventions as an intention of shorten considerable negative experiences. Furthermore, considering nonexistent tool related to Brazilian population, capable of measuring fear before pregnancy, the main objective of this paper was to make a transcultural adaptation and to analyze the evidences of efficacy and reliability for the brazilian version of the Childbirth Fear Prior to Pregnancy (CFPP). Methodology: This study has a methodological manner, approved by the Ethics in Research committee of Medical Science College of Botucatu, under number 2.428.902, with a convenience sample made of 146 nursing graduating students. The Brazilian version for the transcultural adaptation has followed the steps mentioned in the literature. Evaluation by a specialist committee and pre-test with assessment of the target audience. Nevertheless, 146 of nursing graduation students from Medical Science College of Botucatu – FMB and from the Salesians Catholic University Center - UniSALESIANO took part in this study. Data was collected from February to August, 2018, apart from calendar year. Face validity and contents were assessed by a judge committee and by the target audience. The exploratory factorial analysis was made for construct validity. Against validity diverging criteria was tested by the combination of measurements obtained from the Brazilian version of CFPP with subscales of Depression, Anxiety and Stress, of EDAE-A. Additionally, for calculation of internal consistency was made the Cronbach’s Alfa and stability tested through test-retest method. The significance level adopted was 0,05. Results: There were a predominance of female participants with average age of 21,2 years old, without partners, white color skin and with a familiar wage of R$ 3.550,43 in average. Moreover, most of the participants didn’t have a remunerated activity. Furthermore, when separated in college-years, 23,9% were in the first year; 24,6% in the second year; 21,2% in the third year; 20,5% in the fourth year and 10,2% in the fifth year. Most of them hadn’t take the subject about Women Health and had never been to a childbirth before. The factorial analysis shows a factorial solution confirming the one-dimensionality of the instrument. The scores for Brazilian version of CFPP were significantly, however weakly related to the scores of EDAE-A subscale (r=0,32, p<0,001), verifying the efficacy of the criteria. Otherwise, the reliability, was obtained an adequate value for the internal consistency (Cronbach’s Alfa of 0,86). The instrument stability was considered adequate, once values for Intraclass Correlation Coefficient was 0,99 and statistically significant (p=0,000), thus, the results have demonstrated a good temporal stability of the material. Conclusion: According to the analysis of psychometrics properties, the Brazilian version of CFPP is a one-dimensional scale of 10 items, showing good evidences of validity and reliability on measuring the fear of childbirth in young adults before pregnancy. Descriptors: Fear. Nursing. Childbirth. Validation Studies. Psychometry.

Introduction: The nurse has a world acknowledgement on changing birth assistance, recovering birth as a natural process as well as feelings and concerns from parturient being respected. Thus, an interest has been raised on nursing academic graduation. In addition, the meaning as a professional caring about the birthing process can influence the service. Fear, and the interpretation of this period as suffer and pain might stimulate unnecessary interventions as an intention of shorten considerable negative experiences. Furthermore, considering nonexistent tool related to Brazilian population, capable of measuring fear before pregnancy, the main objective of this paper was to make a transcultural adaptation and to analyze the evidences of efficacy and reliability for the brazilian version of the Childbirth Fear Prior to Pregnancy (CFPP). Methodology: This study has a methodological manner, approved by the Ethics in Research committee of Medical Science College of Botucatu, under number 2.428.902, with a convenience sample made of 146 nursing graduating students. The Brazilian version for the transcultural adaptation has followed the steps mentioned in the literature. Evaluation by a specialist committee and pre-test with assessment of the target audience. Nevertheless, 146 of nursing graduation students from Medical Science College of Botucatu – FMB and from the Salesians Catholic University Center - UniSALESIANO took part in this study. Data was collected from February to August, 2018, apart from calendar year. Face validity and contents were assessed by a judge committee and by the target audience. The exploratory factorial analysis was made for construct validity. Against validity diverging criteria was tested by the combination of measurements obtained from the Brazilian version of CFPP with subscales of Depression, Anxiety and Stress, of EDAE-A. Additionally, for calculation of internal consistency was made the Cronbach’s Alfa and stability tested through test-retest method. The significance level adopted was 0,05. Results: There were a predominance of female participants with average age of 21,2 years old, without partners, white color skin and with a familiar wage of R$ 3.550,43 in average. Moreover, most of the participants didn’t have a remunerated activity. Furthermore, when separated in college-years, 23,9% were in the first year; 24,6% in the second year; 21,2% in the third year; 20,5% in the fourth year and 10,2% in the fifth year. Most of them hadn’t take the subject about Women Health and had never been to a childbirth before. The factorial analysis shows a factorial solution confirming the one-dimensionality of the instrument. The scores for Brazilian version of CFPP were significantly, however weakly related to the scores of EDAE-A subscale (r=0,32, p<0,001), verifying the efficacy of the criteria. Otherwise, the reliability, was obtained an adequate value for the internal consistency (Cronbach’s Alfa of 0,86). The instrument stability was considered adequate, once values for Intraclass Correlation Coefficient was 0,99 and statistically significant (p=0,000), thus, the results have demonstrated a good temporal stability of the material. Conclusion: According to the analysis of psychometrics properties, the Brazilian version of CFPP is a one-dimensional scale of 10 items, showing good evidences of validity and reliability on measuring the fear of childbirth in young adults before pregnancy.
Transcultural adaptation and validation of childbirth fear to pregnancy (CFPP) Scale in Brazilian usage
Keywords: Medo; Enfermagem; Parto; Estudos de validação; Psicometria; Fear; Nursing; Childbirth; Validation studies; Psychometry